Expression of mutant patatin protein in transgenic tobacco plants: role of glycans and intracellular location. - Sonnewald, U (1990)
The influence of N-glycosylation and subcellular compartmentation on various characteristics of a vacuolar glycoprotein is described. One member of the patatin gene family was investigated as a model system. Different glycosylation mutants obtained by destroying the consensus site Asn-X-Ser/Thr by oligonucleotide-directed mutagenesis were expressed in leaves of transgenic tobacco plants under the control of a light-inducible promoter. The various patatin glycomutants retained their properties in comparison with the wild-type protein with respect to protein stability, subcellular compartmentation, enzymatic activity, and various physicochemical properties studied showing the N-glycosylation not to be essential for any of these characteristics. To test the importance of the cotranslational transport and the subcellular (vacuolar) location for the properties of the patatin protein, another mutant was constructed in which the signal peptide was deleted, leading to its synthesis and accumulation in the cytosol. Biochemical analysis of this protein in comparison with its vacuolar form again revealed no significant differences with respect to its enzymatic activity or its stability in normal vegetative cells. During seed development, however, the cytoplasmic form was more stable than the vacuolar form, indicating the appearance of proteases specific for the protein bodies of developing seeds.